In-season eccentric-overload training in elite soccer players: Effects on body composition, strength and sprint performance - Suarez-Arrones, L.; Saez de Villarreal, E.; Javier Núñez, F.; Di Salvo, V.; Petri, C.; Buccolini, A.; Maldonado, R. A.; Torreno, N.; Mendez-Villanueva, A. (PLOS ONE, 2018)
The aim of this study was to describe the changes in body composition, strength and sprint performance in response to an entire competitive season of football training supplemented with 2 inertial eccentric-overload training sessions a week in young male professional soccer players. Whole body and regional composition (assessed using dual-energy X-ray absorptiometry), power output in half-squat and 40-m sprinting performance were evaluated in fourteen players. The eccentric-overload training consisted of training sessions a week of 1-2 sets of 10 exercises of upper-body and core (Day 1) and lower-body (Day 2), during the entire competitive season (27 weeks). Whole body fat mass decreased (-6.3 ± 3.6%, ES = -0.99 ± 0.54) substantially while lean mass increased (2.5 ± 0.8%, ES = 0.25 ± 0.09), with some regional differences. There was a substantial increase in half-squat power output (from 3% to 14%, ES from 0.45 to 1.73) and sprint performance (from 1.1% to 1.8%, ES from -0.33 to -0.44), however performance changes were not correlated with changes in body composition. A combined soccer and eccentric-overload training program was able to promote positive changes in body composition and physical factors relevant to both on-field performance and injury prevention in elite soccer players.